Ultra-processed people : why do we all eat stuff that isn't food...and why can't we stop? / Chris van Tulleken. - Tulleken, Chris van, 1978- (Penguin Books, 2024)
We have entered a new 'age of eating' where most of our calories come from an entirely novel set of substances called ultra-processed food - food which is industrially processed and designed and marketed to be addictive. But do we really know what it's doing to our bodies? Join Dr. Chris van Tulleken in his travels through the world of food science and a UPF diet to discover what's really going on.